Development of Pterygoquadrate Complex in the Embryogenesis of the Sand Lizard, Lacerta agilis (Reptilia, Squamata) - Yarygin, A.N. (Вестник зоологии, 2010)
Serial sections of 15 L. agilis embryos on the successive developmental stages, stained with hematoxylin-eosin or alcian blue and hematoxylin-eosin, were examined. It was found that cartilaginous pterygoquadrate complex of L. agilis consists of four parts: quadrate cartilage, pterygoquadrate cartilage, pterygoid process, and processus ascendens. Pterygoquadrate cartilage and pterygoid process are reduced in prenatal ontogenesis, but not earlier than underlying pterygoid bone is developed. The processus ascendens becomes the first cartilaginous parts of this complex, and then the other elements undergo chondrification. Basipterigoid process is formed by two independent parts: aboral part of cranial trabeculas and basipterigoid cartilage. Meniscus pterygoideus is an independent structure, but not a rudiment of the pterygoid process. A previously unrecorded cartilage was revealed and a name basipterigoid cartilage is proposed for it.